An Analysis of Nigeria's Political Leadership: Assessing its Compatibility with Democratic Governance Principles - Felix Chukwudi Onyemachi (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2024)
This paper aims at examining the contradictions in Nigeria’s democratic system of government as they affect the nation’s political leadership. The paper exposes the concept of democracy and some of its core principles that distinguish it from other forms of government. It also confronts some of the devaluating anomalies in Nigeria’s practice of democracy and argues that Nigeria’s political leadership, which ought to be 'people-centric', will not have the desired demonstrative leadership when it is besieged by inequalities, abuse of the rule of law, intimidation, victimization, ethnocentrism, and other forms of violations that are contrary to what democracy stands for. The paper concludes that Nigeria’s political leadership will be successfully geared towards the realization of the common good when the democratic principles that Nigeria’s government falls short of, which also contradict her democratic preference, are checkmated and characteristically adhered to. The paper employs the methods of textual and contextual analysis. The procedure is essentially expository, critical, analytical, and speculative.